Peningkatan Pemahaman Nature of Science (NoS) Siswa Melalui Model Pembelajaran Inkuiri Terbimbing Ditinjau dari Tingkat Efikasi Diri - Hana Lestari (Reslaj : Religion Education Social Laa Roiba Journal, 2020)
ABSTRACT This study aims to (1) know comprehensively the increase in understanding of Nature of Science (NoS) groups of students who obtain guided inquiry learning models and groups of students who receive conventional learning, (2) analyze the criteria for increasing students' NoS understanding among students with self-efficacy levels. high and low. This research is a quasi-experimental study with a 2x2 factorial design. The data analysis technique used was two-way ANOVA with a significance level of 5%. The results showed that the average increase in NOS understanding of students who were given a guided inquiry learning model of 72.6 performed better with the informed category (already knowing and understanding aspects in NOS) while students who received conventional learning were 49.67 included in the category. naïve category (not knowing and understanding aspects in NOS); (2) There is a significant difference in the improvement of students' understanding of NOS between students who get learning with guided inquiry learning models and conventional learning; (3) There is a significant difference in increasing understanding of NOS between students with high self-efficacy tendencies with low self-efficacy, and students with high self-efficacy tendencies are much better at understanding NOS than low self-efficacy; (4) There is an interaction effect between the learning model and the level of self-efficacy together on increasing students' NOS understanding; (5) There is a difference in the improvement of students' understanding of NOS in students who have a tendency towards high self-efficacy who obtain guided inquiry learning models and students who receive conventional learning (6) There are differences in the improvement of students' understanding of NOS in students who have low self-efficacy tendencies who receive guided inquiry learning models and students who receive conventional learning. Keyword: Guided Inquiry, Self efficacy, Understanding NOS